كشف التنظيم الذاتي في استراتيجيات القراءة لدى الناطقين بغير العربية = Identifying self-regulation in reading strategies among non-native speakers of Arabic - Ahmad, Adibah; Mustapha, Nik Hanan; Daud, Nadwah; Mustapha, Nik Farhan (Usuli Faqih Research Centre PLT, 2020)
Self-regulation is a powerful boost in driving students' motivation for learning, because it refers to self-generated thoughts, feelings, and behaviors that aim to achieve goals and students become more self-reliant than teachers, and are hard-working to learn because they understand their strengths and weaknesses. Studies in the field of second and foreign language learning have benefited from the concept of self-regulation and its relation with language learning strategies, and it is called self-regulated learning strategies. Hence, this research aims to determine to what extent those students use self-regulated learning strategies to read texts in Arabic, and it is measured based on three basic meta-strategies; planning, observation, and evaluation. This research was based on the qualitative method by using semi-structured interview for data collection and the respondents are six female students majoring in Arabic language from International Islamic University in Malaysia. This research has identified that students used self-regulated learning strategies during reading in Arabic in all aspects of planning, observation and evaluation strategies in which planning is the most strategies used by the respondents. In conclusion, the research recommended that students should be interested in using self-regulation to improve reading skills in Arabic, thus ensuring life-long learning.